Objective Requirements for an Effective Transition to a Green Economy - FLORIN BONCIU (Global Economic Observer)
The paper presents a critical analysis of the current approaches of the transition to a green economy also known as a “net zero” economy. The analysis is based on the identification of two hard constraints (defined as “availability condition” and “affordability condition”). The analysis puts into perspective previous technological and energy transitions that happened due to technological and market economy forces with administrative / volitive transitions in which significant changes of the economic and social environment are intended resulting from changes in the rules of the game and from mandatory standards. In this context, the paper presents several clarifications and recommendations that should be considered in order to achieve an effective and efficient transition without incurring societal and economic consequences.